One World for Good or Ill: The Impact of Globalization on Mineral Exploration - Warin, Oliver (Geoscience Canada, 2000)
Summary Just as the year 1500 indexed the arrival of One Europe so the year 2000 seems to be indexing the arrival of One World. We can now, if we so choose, explore for minerals over the whole world. We need to learn the lessons of the past, and looking back at four outstanding discoveries of Company Maker deposits it seems that a tenacious geologist with a good exploration idea and a convinced, sympathetic exploration manager to keep the funding flowing may be important ingredients. Experience suggests that there are three species of geoscientists in mineral exploration: the scientific aristocrats who ask How? and want to study the genesis of deposits; the tradesmen who ask Where? and expect to find the next one by association; and the criminal investigators who ask What? and are convinced a deposit will be revealed by the clues the deposit itself leaves. The bulk of the members of a successful mineral exploration team will be tradesmen: most exploration discoveries arc made by association.For mineral exploration to provide the excitement, the challenge, and the fun it deserves, the emphasis must be on the risky game of prediction rather than on the safe, secure world of description.